Dabiq: A study of the usage of terrorist-produced publications in framing and selective moral disengagement - Khalil, Nouran Hussein Mohamed Hussein (AUC Knowledge Fountain, 2017)
Dabiq, the official English language publication of ISIS, the Islamic State in Iraq and Syria, has been widely circulated online, and has gained a relatively large audience. The study discusses the ways in which the Islamic State of Iraq and Syria (ISIS) uses their official publication, Dabiq, to promote its objectives and to spread terror. In this study, a content analysis is conducted to examine terrorist rhetoric in the magazine and its mediation for the sake of fulfilling the group’s objectives. The study uses two main theories: the theory of framing analyzing how ISIS frames itself, its supporters and its opponents, and the theory of selective moral disengagement, analyzing the mechanisms ISIS uses through Dabiq to morally disengage their soldiers and supporters, thus allowing them to commit more violent acts without exercising their moral agency or feeling empathetic towards their victims. The content analysis was conducted on the whole Dabiq population (15 issues, containing 206 articles). The findings show that ISIS attempts to frame itself as a caliphate and a state, and a gateway to heaven, and its fighters and supporters as moral agents, and fighters for God, as opposed to the framing of their opponents and victims, which were framed as enemies of God. The interesting finding was that all supporters and fighters of ISIS are very strategically framed as part of the in-group, while all opponents and victims are framed as part of the out-group. On the other hand, when analyzing the rhetoric of the magazine from the perspective of the theory of selective moral disengagement, the findings suggest that all 7 mechanisms of moral disengagement are very significantly present in the rhetoric of the magazine, with the most used mechanism in the magazine, moral justification, being present in 97% of the total population of the magazine, and least mechanism used, dehumanization of victims, being present in 41% of the total population of the magazine. Through the study, it was found that ISIS attempts to assemble a united political identity for itself and its followers by means of framing the in-group and out-group, and morally disengaging its in-group to keep it loyal, supportive and active towards achieving its cause and purpose, and to have it enforce its attitudes of rejection and vicious behavior towards the out-group.